Determination of Free Trade Zone and Free Port Development Area Development in Batam City, Riau Islands, Indonesia - Indera, Edi; Sihombing, Marlon; Muluk, Chairul; ., Rujiman (International Journal of Engineering and Technology, 2018)
Batam Island is built into the Free Trade since 1970 by the Batam Authority, but in 2000 stood Batam City Government, to 2016 the economy grew 6,5%, but since 2017 dropped to 2%, this phenomenon should be a study. The population is employee environment Batam Area Concession Agency, APINDO, BKPM, Batam City Government Employees, the Chamber of Commerce, Community and students. Total respondents 190 respondents sampled (census method). Data Analysis was perfomed using Structural Equation Model (SEM). The software used for the structural analysis is AMOS 22, descriptive analysis using SPSS version 22.0. Geographical Utilization variable determination to variable investmenthas standardized estimate of 0,121
Keywords: Geographical Location; Infrastructure; Organizational Resources; Investment and Regional Development